SELF-DISCOVERY: PSYCHOANALYSIS OF THE FILM BOHEMIAN RHAPSODY (2018) - Rudy, Rudy; Samosir, Irvan Ricardo .N.; Hutabarat, Landa Kro (Universitas Putera Batam, 2022)
This study focuses on the discussion of self-discovery and its depiction reflected in the film Bohemian Rhapsody (2018). This study is expected to be able to contribute in completing the theory in the fields of culture, literature, media, etc. and to enrich people’s knowledge of self-discovery. The objective of this library research is to identify the concept of self-discovery as well as to analyze the issue of self-discovery portrayed in the film. The primary data needed for analysis was acquired from dialogs along with the descriptions of film scenes. This study used Freud’s psychoanalytic approach to analyze the data. From the psychoanalysis point of view, the results of the study suggested that self-discovery is strongly related to one’s self - a person’s life journey to search for his true self or the life he wants. The results of analysis also showed that self-discovery was portrayed in the film through several images such as a unique style or physical appearance, loneliness and disclosure of sexual orientation.